The strategic interplay in academia: administrators versus students. (5th March 2020) - Islam, Md. Sariful; Afrin, Sonia; Das, Debasish Kumar; Ahsan, Md. Nasif
Abstract : Purpose: This paper aims to study students' strategic behaviors for increasing their job prospect in response to university administrators' moves for lifting up institutional reputation in the academia. Design/methodology/approach: A Stackelberg differential game is used to study this strategic interplay between administrators and students. In this game, an administrator maximizes institutional quality to build university reputation while student maximizes grades to increase their job prospects. Therefore, administrators being the leader move first while students set strategies for maximizing their objective function by following administrators' move. Findings: The study produces several distinctive results by analyzing administrator–students' strategic interactions. First, university administrators need to be sufficiently more impatient for building reputation by improving institutional quality than students' impatience for increasing their job prospects to have feasible solutions. Second, students attempt to increase academic grades for making them more marketable in response to administrators' additional efforts for increasing their students' job prospects. Third, exogenous increase in university reputation improves institutional quality and students' job prospects without affecting their academic grades. However, increase in job prospects motivates students to increase their grades. Fourth, administrators' too much impatience for increasing university reputation could inflate students' grade, reduce job prospect and degrade institutional quality. Fifth, an exogenous rise in students' impatience improves institutional quality and students' job prospects but reduces students' grades. Finally, the exogenous increase in opportunity cost of securing good grade degrades institutional quality, thus reducing further job prospects. Therefore, administrators' positive but moderate impatience for reputation will improve students' academic performances, institutional quality and job prospects. Originality/value: To the best of the authors' knowledge, this is the first study to analyze students' strategic responses for improving their job prospects in response to administrators' actions for enhancing university reputation. It helps administrators to design an effective framework for building university reputation in the academic market through improving institutional quality and expanding job markets for their students.